1990
DOI: 10.1149/1.2086348
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Carbon Composite Materials from Fiber Precursors: I . Preparation of Stainless Steel—Carbon Composite Electrodes

Abstract: A novel approach to fabrication of composite metal‐carbon electrodes has been developed. Stainless steel fibers (2 μm diam) and carbon fiber bundles (20 μm diam) were combined with cellulose (as the binding agent) into an interwoven paper preform. The composite paper preform was then sintered to a stainless foil substrate to form the electrode structure. “Optimal sintering,” experimentally determined by the percentage of initial carbon remaining in the sintered electrode, was achieved at 1423 K in H2 for 2.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The VGCFs were consequently chosen as the applicable nanofibers for this novel filter media fabrication in our laboratories. , The large van der Waals force and high surface energy between VGCFs cause bundling of the VGCFs with bundles ranging in diameter from a few hundred microns to a few millimeters. Based on the method developed by the Auburn CM3 group, the VGCFs have been successfully separated, flocked, and dispersed into the wet-laid nonwoven filtration media with polymers and activated carbon fibers. The nonwoven nanofloc filter media has been successfully developed by embedding nanoflocs into microfiber support structures via a wet-lay process.…”
Section: Introductionmentioning
confidence: 99%
“…The VGCFs were consequently chosen as the applicable nanofibers for this novel filter media fabrication in our laboratories. , The large van der Waals force and high surface energy between VGCFs cause bundling of the VGCFs with bundles ranging in diameter from a few hundred microns to a few millimeters. Based on the method developed by the Auburn CM3 group, the VGCFs have been successfully separated, flocked, and dispersed into the wet-laid nonwoven filtration media with polymers and activated carbon fibers. The nonwoven nanofloc filter media has been successfully developed by embedding nanoflocs into microfiber support structures via a wet-lay process.…”
Section: Introductionmentioning
confidence: 99%
“…) shows the SEM image of as-received VGCF clumps that were dispersed and then flocked. The SEM images of the final sintered nickel nonwovens with varying quantities of VGCF are shown in figures 5(b)-(e).One concern during metal nonwoven sintering was the catalytic gasification of entrapped carbon[23][24][25]. The sintering conditions were simulated in a thermal gravimetric analyzer (TGA) to check for the loss of VGCF due to catalytic gasification.…”
mentioning
confidence: 99%
“…Tatarchuk et al 13,14 recently have reported the development and preliminary characterization of a stainless steelcarbon composite electrode which combines the high surface area of activated carbon fibers with the high conductivity of stainless steel fibers into a self-supporting sintered network. The electrodes are highly permeable to liquids and gases and have excellent electrical conductivity.…”
mentioning
confidence: 99%